Aesthetic Presence Hypothesis of the Role Character in the Actor's Theatrical Performance: يــاسين إسماعيل خلـف (Al-Academy, 2020)
The current study monitors the mechanisms of formation of the actor's performance expressive system (voice and motion) and the levels of their construction consistent with the aesthetic premise of the theatrical performance through incorporating what is natural, materialistic (physiological) and artistic and philosophical virtual (aesthetic ), through which the creative actor seeks not to repeat the image and substance of a thing according to its natural life image, in favor of new aesthetic reproduction governed by a group of significant relationships formed according to (artistic and philosophical) characteristics and features that distinguish the artistic accomplishment from its reality(its natural and functional reference). According to the data of its virtual presence and the ways of role character construction and its connections with the aesthetic premise of the show, our research monitors the mechanisms of achieving the actor's expressive system and addresses the properties and features of their (skilled) artistic and philosophical construction, aimed at identifying and discovering the aesthetic distance between the (physiological) presence of the actor's body and his artistic and philosophical (cultural ) presence being an effective indicative sign. The research concluded with the following results: • The actor's presence has various levels related to the nature and variables of the aesthetic relationship between the natural and subjective data of the actor, and the (aesthetic) data of the role character on the one hand, and their relationships with the aesthetic premise of the show on the other hand. • The actor's presence becomes clear in the creative manifestation process within three compatible levels. The external level: materialistic, natural (physiological), the internal level (psychological) and an objective aesthetic level (artistic, philosophical)